Front Cover: ABC–ABC‐Type Directly meso–meso Linked Porphyrin Dimers (Chem. Eur. J. 2/2019). Issue 2 (18th December 2018) - Higashino, Tomohiro; Kurumisawa, Yuma; Iiyama, Hitomi; Imahori, Hiroshi
Abstract : Meso‐meso directly linked porphyrin oligomers reveal unique photophysical properties due to their strong exciton couplings derived from alternative orthogonal geometry of the porphyrins. Although their structural and electronic properties can be greatly altered by substituents at meso ‐positions, it is still difficult to introduce very different substituents at the meso ‐positions. This work develops a general synthetic strategy for meso ‐ABC‐ABC‐type meso – meso directly linked porphyrin dimers. The cover picture shows a meso ‐ABC‐ABC‐type meso – meso linked donor‐π‐acceptor‐type porphyrin dimer, which exhibits the highest power conversion efficiency (7.91%) ever reported for dye‐sensitized solar cells based on dimeric orthogonal donor‐π‐acceptor‐type organic sensitizers. More information can be found in the Full Paper by H. Imahori et al. onpage 538 .